English Consonants Production on School-Age Children - Monoarfa, Muchlik Kamal; Ali, Sri Widyarti; Bay, Indri Wirahmi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
This study aims to reveal the production of consonant sounds in children aged 6-9 years old whose first language is Indonesian and/or Gorontalo language, as well as to reveal the facts about the consonant sounds that can and cannot be produced by the children. This study applied qualitative method by collecting the data using audio and video recording to record the consonant sounds produced by the participants, and transcribing the sounds using IPA (International Phonetic Alphabet). The data of this study were taken from School-Age Children from six until nine years old, that consisted of five students from Ronal Hutagalung Learning Center. The data analysis was carried out through the stages of data reduction, data display, and the drawing and verifying conclusion. Furthermore, the classification of NAE Consonant Phonemes by Parker (1986) was used as the main theory in data analysis. The findings show that from five participants, three participants can produce 23 consonant sounds, and two participants can produce 24 consonant sounds. In addition, the results also show that the participants were mostly unable to produce consonants Voiceless Dental Fricative /θ/, Voiced Palatal Fricative /ʒ/, Voiced Palatal Glide /y/, Voiceless Palatal Fricative /ʃ/, and Voiced Dental Fricative /ð/, which means that most of the sounds that they cannot produce are the consonants that do not exist in their first language. The findings of this study are expected to be a reference in teaching English pronunciation to children, as well as overcoming the problems related to the consonant production in children. Penelitian ini bertujuan untuk mengungkap produksi bunyi-bunyi konsonan pada anak usia 6-9 tahun yang bahasa pertamanya adalah bahasa Indonesia dan/atau bahasa Gorontalo, serta mengungkap fakta tentang bunyi konsonan yang dapat dan tidak dapat dihasilkan oleh anak pada usia tersebut. Penelitian ini menggunakan metode kualitatif dengan pengumpulan data menggunakan rekaman audio dan video untuk merekam bunyi konsonan yang dihasilkan oleh partisipan, dan mentranskripsi bunyi-bunyi tersebut dengan menggunakan IPA (International Phonetic Alphabet). Data penelitian ini diambil dari Anak Usia Sekolah dari usia enam sampai sembilan tahun, yang terdiri dari lima siswa dari Ronal Hutagalung Learning Center. Analisis data dilaksanakan melalui tahapan reduksi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Selanjutnya, klasifikasi Fonem Konsonan NAE oleh Parker (1986) digunakan sebagai teori utama dalam analisis data. Hasil penelitian menunjukkan bahwa dari lima partisipan, tiga partisipan dapat menghasilkan 23 bunyi konsonan, dan dua partisipan dapat menghasilkan 24 bunyi konsonan. Selain itu, hasil penelitian juga menunjukkan bahwa sebagian besar partisipan tidak dapat memproduksi konsonan Voiceless Dental Fricative /θ/, Voiced Palatal Fricative /ʒ/, Voiced Palatal Glide /y/, Voiceless Palatal Fricative /ʃ/, and Voiced Dental Fricative /ð/, yang berarti bahwa sebagian besar bunyi yang tidak dapat mereka lafalkan adalah konsonan yang tidak ada dalam bahasa pertama mereka. Temuan penelitian ini diharapkan dapat menjadi acuan dalam mengajarkan pronunciation bahasa Inggris pada anak, serta mengatasi permasalahan terkait produksi bunyi-bunyi konsonan pada anak.